Wilhelm Dilthey’s Historicism and Its Relevance Today - Pranowo, Hendrikus Ageng (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
The relationship between humans and their world requires understanding. This project is not only concerned with the existential search for the meaning and purpose of human existence. However, the first question is how objective knowledge can be acquired. In addressing this, knowledge enables humans to comprehend the meaning and purpose of their existence. Examining humans and their relationship with the world has never been separated from studying existential phenomenology. However, this problem also needs to be seen from an epistemological perspective. This article attempts to offer an alternative framework for understanding humans’ relationship with their world and how objective knowledge can be acquired. In addressing this, Wilhelm Dilthey’s historicism philosophy becomes pertinent for contemporary discourse. Dilthey’s critique of historical reasoning aims to illustrate that truth within existential and epistemological contexts is historically situated. Consequently, by critiquing history, not only is it demonstrated that objective knowledge can be pursued, but also that humans can fathom the meaning and purpose of their existence concerning their world.